Coronary computed tomography angiography investigation of the association between left main coronary artery bifurcation angle and risk factors of coronary artery disease - Temov, K.; Sun, Zhonghua (Springer Netherlands, 2016)
To explore the association between the left main coronary artery bifurcation angle and common atherosclerotic risk factors with regard to the development of coronary artery disease (CAD) using coronary computed tomography angiography (CCTA). A retrospective review of 196 CCTA cases (129 males, 67 females, mean age 58 ± 10.5 years) was conducted. The bifurcation angle between the left anterior descending (LAD) and left circumflex (LCx) was measured on two-dimensional (2D) and three-dimensional (3D) reconstructed images and the type of plaque and degree of lumen stenosis was assessed to determine the disease severity. An association between bifurcation angle and patient risk factors [gender, body mass index (BMI), hypertension, cholesterol, diabetes, smoking and family history] of CAD was also assessed to demonstrate the relationship between these variables. The mean bifurcation angle between the LAD and LCx was 79.40° ± 22.97°, ranging from 35.5° to 178°. Gender and BMI were found to have significant associations with bifurcation angle. Males were at 2.07-fold greater risk of having a >80° bifurcation angle and developing CAD than females (P = 0.003), and patients with high BMI (>25 kg/m2) were 2.54-fold more likely to have a >80° bifurcation angle than patients with a normal BMI (P = 0.001) and thus were at greater risk of developing CAD. There is a direct relationship between the left main coronary artery bifurcation angle and patient gender and BMI. Measurement of the bifurcation angle should be incorporated into clinical practice to identify patients at high risk of developing CAD.